Carbon-based nano material for improving salt tolerance of wheat as well as preparation method and application of carbon-based nano material

By preparing carbon-based nanomaterials D-CDs and using their ability to catalyze active oxygen to activate the defense system of wheat seeds, the high cost and environmental risk problems of existing metal-based nanomaterials in improving wheat salt tolerance have been achieved. Improvement of efficient salt tolerance of wheat in high-salt environment.

CN119306211APending Publication Date: 2025-01-14XINJIANG UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411638275.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-16
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing metal-based nanomaterials have high costs and potential ecological and environmental risks in improving crop stress resistance, and it is difficult to effectively improve the salt tolerance of wheat in high-salt environments.

Method used

Using carbon-based nanomaterials, D-CDs nanomaterials are prepared by ultrasonic mixing of sulfur-containing biomass carbon source materials, strong oxidants and alkaline solutions in deionized water, followed by hydrothermal reaction and dialysis. This material can regulate the content of active oxygen during the seed presoaking process, activate the seed's defense system, and improve the salt tolerance of wheat.

Benefits of technology

This method is simple, safe and easy to control, suitable for large-scale production, and the materials are bio-friendly, reducing the risk of heavy metal contamination. It can significantly improve the germination rate, root and stem length of wheat in high-salt environments, and reduce soil salinity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306211A_ABST
    Figure CN119306211A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a carbon-based nano material for improving salt tolerance of wheat, which comprises the following steps: ultrasonically and uniformly mixing a sulfur-containing biomass carbon source material, a strong oxidant and an alkaline solution in deionized water to obtain a mixed solution, carrying out hydrothermal reaction on the mixed solution, and cooling to room temperature after the reaction to obtain a reaction solution; and sequentially filtering and dialyzing the reaction liquid to obtain the carbon-based nano material D-CDs. The invention also provides application of the carbon-based nano material prepared by the preparation method, the carbon-based nano material is applied to pre-seed soaking of wheat before sowing, and the stress resistance of the wheat under a high-salt growth condition is improved. The preparation process of the carbon-based nano material is simple and easy to control, the raw material cost is low, the carbon-based nano material is biologically friendly, and an effective solution is provided for relieving germination of wheat in a high-salt environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanomaterials and their application in improving crop stress resistance, and particularly relates to a carbon-based nanomaterial for improving wheat salt tolerance, a preparation method and an application thereof. Background Art

[0002] Soil salinization is a growing global problem, posing a significant threat to crops. Seeds are the starting point of a plant's life cycle, and seed germination is a critical stage affecting crop yield and quality. High salinity can reduce seed germination rate and quality, threatening subsequent seedling development and affecting crop yield. Therefore, improving seed stress resistance is key to promoting crop growth and reducing yield losses, and is crucial to safeguarding global food production.

[0003] Plants have evolved complex defense systems to cope with external disturbances. These defense systems can be pre-activated before exposure to stress, enabling them to mount a more rapid and robust defense response in the event of subsequent stress. Reactive oxygen species (ROS) are key signaling molecules that activate defense systems. Therefore, modulating intracellular ROS levels is one approach to enhance seed stress tolerance. Nanomaterials, due to their unique physicochemical properties, have the ability to catalyze ROS production. Their small size allows nanoparticles to easily penetrate the biological barrier of the seed coat and regulate ROS levels within the seed. Studies have shown that nanoparticles such as AgNPs, TiO2, and FeNPs can catalyze ROS production. AgNPs can exhibit POD-like activity within rice cells, increasing intracellular ROS levels and activating defense systems, reprogramming defense-related metabolites and genes, and enhancing seed salt tolerance. However, current materials are mostly metal-based, which poses high costs and potential ecological risks, limiting their application.

[0004] Carbon dots (CDs) are zero-dimensional nanomaterials with advantages such as easy synthesis, low cost, and low toxicity. Previous studies have shown that CDs can promote plant photosynthesis and nutrient uptake. Furthermore, CDs modified with various chemical modifications can catalyze the generation or scavenging of ROS.

[0005] Based on this, a biomass carbon-based nanomaterial for improving the salt tolerance of wheat and its preparation method and application are proposed. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to address the deficiencies of the above-mentioned existing technologies and provide a carbon-based nanomaterial and its preparation method and application for improving the salt tolerance of wheat. The carbon-based nanomaterial prepared by the present invention regulates the content of active oxygen in seeds during pre-soaking, activates the defense system of the seeds, and puts the seeds in a defensive state before facing stress, thereby alleviating the stress suffered by the seeds in a high-salt environment and improving the salt tolerance of the seeds.

[0007] To solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a carbon-based nanomaterial for improving the salt tolerance of wheat, the preparation method comprising the following steps:

[0008] S1. Ultrasonic mixing of a sulfur-containing biomass carbon source material, a strong oxidant, and an alkaline solution in deionized water to obtain a mixed solution;

[0009] S2, subjecting the mixed solution obtained in S1 to a hydrothermal reaction, and cooling the mixture to room temperature after the reaction to obtain a reaction solution;

[0010] S3. The reaction solution obtained in S2 is filtered and dialyzed in sequence to obtain a carbon-based nanomaterial, which is named D-CDs.

[0011] Preferably, the mass volume ratio of the sulfur-containing biomass carbon source material, the strong oxidant, the alkaline solution and the deionized water in S1 is (0.1-0.3) g: (0.3-1) mL: (0.3-1) mL: (18-28) mL.

[0012] Preferably, the sulfur-containing biomass carbon source material is one or more of straw powder, seaweed, garlic and durian shell powder; the strong oxidant is a hydrogen peroxide solution with a mass fraction of 20.00-40.00% or a potassium permanganate solution with a mass fraction of 1.00-3.00%; the alkaline solution is a 0.5-1.6 mol·L -1 Sodium hydroxide solution with a concentration of 0.1-0.4 mol·L -1 of potassium hydroxide solution or ethylenediamine.

[0013] Preferably, the temperature of the hydrothermal reaction in S2 is 150-200° C., and the time is 4-8 hours.

[0014] Preferably, the dialysis membrane used in the dialysis in S3 has a specification of 1000 Da, and the dialysis time is 3-5 h.

[0015] The present invention also provides a carbon-based nanomaterial for improving the salt tolerance of wheat, which is prepared by the above-mentioned method for preparing the carbon-based nanomaterial for improving the salt tolerance of wheat.

[0016] The present invention also provides an application of a carbon-based nanomaterial capable of improving salt tolerance of wheat in wheat germination under a high-salt environment.

[0017] Preferably, the salt content of the high-salt environment is 50-200 mmol·L -1 .

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] 1. The carbon-based nanomaterials prepared in the present invention have a simple preparation process, safe and easy-to-control reaction conditions, and are suitable for large-scale production.

[0020] 2. The carbon-based nanomaterials prepared in the present invention use sulfur-containing biomass carbon sources as raw materials, are bio-friendly, widely available, easily obtainable, and less polluting. They improve the salt tolerance of wheat while reducing the risk of heavy metal pollution.

[0021] 3. The carbon-based nanomaterial prepared in the present invention only requires one soaking step for wheat seeds, and there is no subsequent operation step. The method of use is simple and easy to operate, and is suitable for popularization and use.

[0022] 4. The wheat roots treated with the carbon-based nanomaterials prepared in the present invention have a certain salt-accumulating effect, which enables the wheat to absorb salt from the surrounding environment and plays a certain role in reducing soil salinity.

[0023] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 1 and 2 are high-resolution TEM images and particle size distribution diagrams of the D-CDs obtained in Example 1.

[0025] Figure 2 is the full scan XPS spectrum of the D-CDs obtained in Example 1.

[0026] Figure 3 This is the C1s scanning XPS spectrum of the D-CDs obtained in Example 1.

[0027] Figure 4 This is the N1s scanning XPS spectrum of the D-CDs obtained in Example 1.

[0028] Figure 5 This is the O1s scanning XPS spectrum of the D-CDs obtained in Example 1.

[0029] Figure 6 This is the FT-IR spectrum of the D-CDs obtained in Example 1.

[0030] Figure 7 These are Raman spectra of the D-CDs, D-CDs pre-preg seed slices, and water pre-preg seed slices obtained in Example 1.

[0031] Figure 8 The graphs are the growth diagrams of wheat with or without the use of D-CDs obtained in Example 1.

[0032] Figure 9 This is a graph showing the germination rate of wheat grown with or without the use of D-CDs obtained in Example 1.

[0033] Figure 10 This is a graph showing the root and stem lengths of wheat grown with or without the D-CDs obtained in Example 1.

[0034] Figure 11 This is a graph showing the malondialdehyde content in roots and stems of wheat grown with or without the D-CDs obtained in Example 1.

[0035] Figure 12 This is a graph showing the total antioxidant capacity of wheat roots and stems with or without the use of D-CDs obtained in Example 1.

[0036] Figure 13 This is a graph showing the sodium ion content in the roots of wheat grown with or without the use of D-CDs obtained in Example 1. DETAILED DESCRIPTION

[0037] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0038] Example 1

[0039] This embodiment provides a method for preparing a carbon-based nanomaterial for improving salt tolerance of wheat, the preparation method comprising the following steps:

[0040] S1, 0.3g of durian shell powder with a particle size of 20 mesh, 1mL of 30% hydrogen peroxide solution and 1mL of 1mol·L -1 The sodium hydroxide solution was ultrasonically mixed in 25 mL of deionized water to obtain a mixed solution;

[0041] S2. Transfer the mixed solution obtained in S1 to a 50 mL Teflon-lined stainless steel autoclave, perform a hydrothermal reaction at 180° C. for 5 h, and cool to room temperature (25° C.) after the reaction to obtain a reaction solution;

[0042] S3. The reaction solution obtained in S2 was first filtered using a membrane filter with a diameter of 0.22 μm, and then dialyzed in new deionized water using a dialysis membrane with a molecular cutoff of 1000 Da for 3 h to obtain carbon-based nanomaterials (D-CDs).

[0043] The microstructure of the D-CDs obtained in this example was analyzed by TEM. Figure 1As shown, the carbon dots are quasi-spherical and monodisperse. Among the approximately 100 particles analyzed, the average size of these particles is about 4.83 nm, and the lattice spacing of D-CDs is about 0.18 nm.

[0044] In order to determine the structural characteristics of the D-CDs obtained in this example, the chemical composition and bonding arrangement of the D-CDs were analyzed using XPS. The XPS survey spectrum of the D-CDs showed that the D-CDs were mainly composed of C, O, and N elements, with C accounting for 62.98%, O accounting for 33.14%, and N accounting for 3.16% ( Figure 2 In the high-resolution C1s XPS spectrum ( Figure 3 There are three main peaks at 284.09eV, 285.33eV and 287.5eV, which are CC / C=C, CO / CS and C=O / C=N respectively. The N 1sXPS spectrum ( Figure 4 There are two main peaks at 399.64eV and 397.9eV, which are N-C3 and pyridine N, C=O and CO O1s XPS spectrum ( Figure 5 The results show that the carbon dots of the carbon-based nanomaterials prepared in this example are rich in functional groups such as carbonyl, amino and hydroxyl groups.

[0045] The FT-IR spectrum of the D-CDs prepared in this example is as follows: Figure 6 As shown. At about 651cm -1 Absorption peaks corresponding to CS vibration stretching were observed at approximately 1410 cm -1 and 1609cm -1 The absorption peaks indicating the presence of C=C and C=N groups were observed at approximately 3427 cm -1 Peaks corresponding to OH and NH vibration stretching were observed at , indicating that there are a large number of amino and hydroxyl groups on the surface of D-CDs, thus having good hydrophilicity.

[0046] The D-CDs prepared in this example can penetrate the seed epidermis and enter the interior of the seed. Figure 7 As shown in Figure 3, we observed Raman peaks similar to those in the material itself inside the D-CDs pre-soaked seeds, while such peaks were not produced inside the seeds themselves.

[0047] Conduct application and comparative experiments:

[0048] like Figure 8-11 As shown, Figure 8A plus sign (+) indicates addition, and a minus sign (-) indicates no addition. Wheat seeds were pre-soaked with the carbon-based nanomaterials (D-CDs) prepared in this example and pure water for 24 hours. The seeds were then germinated on filter paper with or without salt, with five parallel groups set up. Under a high-salt environment (100 mM salt), wheat seeds pre-soaked with D-CDs exhibited a higher germination rate (from 90.0% to 97.7%), longer roots (increased by 9.8%), and longer stems (increased by 9.4%) over a 7-day germination period.

[0049] like Figure 12 and Figure 13 The wheat seeds pre-soaked with the carbon-based nanomaterials prepared in this example showed lower malondialdehyde content and higher total antioxidant capacity in both roots and stems, and the wheat roots had a certain salt accumulation capacity.

[0050] Example 2

[0051] This embodiment provides a method for preparing a biomass carbon-based nanomaterial that improves salt tolerance of wheat, comprising the following steps:

[0052] S1, 0.1g of straw powder with a particle size of 20 mesh, 0.3mL of 20% hydrogen peroxide solution and 0.3mL of 1.5mol·L -1 The sodium hydroxide solution was ultrasonically mixed in 18 mL of deionized water to obtain a mixed solution;

[0053] S2. Transfer the mixed solution obtained in S1 to a 50 mL Teflon-lined stainless steel autoclave, perform a hydrothermal reaction at 180° C. for 5 h, and cool to room temperature (25° C.) after the reaction to obtain a reaction solution;

[0054] S3. The reaction solution obtained in S2 was first filtered using a membrane filter with a diameter of 0.22 μm, and then dialyzed in new deionized water using a dialysis membrane with a molecular cutoff of 1000 Da for 3 h to obtain carbon-based nanomaterials (D-CDs).

[0055] Conduct application and comparative experiments:

[0056] Wheat seeds were pre-soaked with the carbon-based nanomaterials prepared in this example and pure water for 24 hours, then germinated on filter paper with or without salt. Five parallel groups were set up. Under a high-salt environment with a salt content of 200 mM, wheat seeds pre-soaked with D-CDs showed a higher germination rate (from 80.0% to 89.4%), longer roots (increased by 9.3%), and longer stems (increased by 8.6%) over a 7-day germination period.

[0057] The concentration of the sodium hydroxide solution in this embodiment S1 can also be 0.5 mol·L -1 , 0.6 mol·L-1 , 0.7 mol·L -1 , 0.8 mol·L -1 , 0.9 mol·L -1 , 1.0 mol·L -1 , 1.1 mol·L -1 , 1.2 mol·L -1 , 1.3 mol·L -1 , 1.4 mol·L -1 or 1.6 mol·L -1 .

[0058] Example 3

[0059] This embodiment provides a method for preparing a biomass carbon-based nanomaterial that improves salt tolerance of wheat, comprising the following steps:

[0060] S1. Ultrasonic mixing of 0.2 g of 20-mesh straw powder, 0.7 mL of 20% hydrogen peroxide solution, and 0.7 mL of ethylenediamine solution in 28 mL of deionized water to obtain a mixed solution;

[0061] S2. Transfer the mixed solution obtained in S1 to a 50 mL Teflon-lined stainless steel autoclave, perform a hydrothermal reaction at 180° C. for 5 h, and cool to room temperature (25° C.) after the reaction to obtain a reaction solution;

[0062] S3. The reaction solution obtained in S2 was first filtered using a membrane filter with a diameter of 0.22 μm, and then dialyzed in new deionized water using a dialysis membrane with a molecular cutoff of 1000 Da for 3 h to obtain carbon-based nanomaterials (D-CDs).

[0063] Conduct application and comparative experiments:

[0064] Wheat seeds were treated with the carbon-based nanomaterials prepared in this example and pure water for 24 hours before being germinated on filter paper with or without salt. Five parallel groups were set up. Under a high-salt environment with a salt content of 50 mM, wheat seeds pre-soaked with D-CDs showed a higher germination rate (from 92.3% to 98.5%), longer roots (increased by 8.4%), and longer stems (increased by 7.8%) over a 7-day germination period.

[0065] The mass fraction of the hydrogen peroxide solution in S1 of this embodiment can also be 22%, 23%, 25%, 27%, 28%, 29%, 31%, 33%, 35%, 36%, 37%, 38%, 39% or 40%.

[0066] Example 4

[0067] This embodiment provides a method for preparing a biomass carbon-based nanomaterial that improves salt tolerance of wheat, comprising the following steps:

[0068] S1, 0.2g seaweed, 0.8mL of 2.0% potassium permanganate solution and 0.8mL of 0.3mol·L -1 The potassium hydroxide solution was ultrasonically mixed in 26 mL of deionized water to obtain a mixed solution;

[0069] S2. The mixed solution obtained in S1 was transferred to a 50 mL Teflon-lined stainless steel autoclave, and a hydrothermal reaction was carried out at a temperature of 150° C. for 8 h. After the reaction, the mixture was cooled to room temperature (25° C.) to obtain a reaction solution;

[0070] S3. The reaction solution obtained in S2 was first filtered using a membrane filter with a diameter of 0.22 μm, and then dialyzed in new deionized water using a dialysis membrane with a molecular cutoff of 1000 Da for 4 hours to obtain carbon-based nanomaterials (D-CDs).

[0071] In this embodiment S1, garlic can also be used as the sulfur-containing biomass carbon source material, the mass fraction of the potassium permanganate solution can also be 1.0%, 1.1%, 1.2%, 1.3%, 1.5%, 1.7%, 1.9%, 2.3%, 2.4%, 2.5%, 2.7%, 2.8%, 2.9% or 3.0%, and the concentration of the potassium hydroxide solution can also be 0.1 mol·L -1 , 0.2 mol·L -1 or 0.4 mol·L -1 ; The temperature of the hydrothermal reaction in S2 can also be 152°C, 155°C, 160°C, 165°C, 170°C, 175°C, 179°C, 185°C, 190°C, 195°C or 200°C, and the reaction time can also be 4h, 4.5h, 5.5h, 6h, 6.5h, 7h, 7.5h or 7.9h.

[0072] Example 5

[0073] This embodiment provides a method for preparing a biomass carbon-based nanomaterial that improves salt tolerance of wheat, comprising the following steps:

[0074] S1, 0.1g seaweed, 0.1g straw powder with a particle size of 20 mesh, 0.8mL of 1.0% potassium permanganate solution and 0.8mL of 0.3mol·L -1 The potassium hydroxide solution was ultrasonically mixed in 27 mL of deionized water to obtain a mixed solution;

[0075] S2. The mixed solution obtained in S1 was transferred to a 50 mL Teflon-lined stainless steel autoclave, and a hydrothermal reaction was carried out at a temperature of 185° C. for 6 h. After the reaction, the mixture was cooled to room temperature (25° C.) to obtain a reaction solution;

[0076] S3. The reaction solution obtained in S2 was first filtered using a membrane filter with a diameter of 0.22 μm, and then dialyzed in new deionized water using a dialysis membrane with a molecular cutoff of 1000 Da for 5 h to obtain carbon-based nanomaterials (D-CDs).

[0077] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent variation made to the above embodiment based on the essence of the invention technology shall still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a carbon-based nanomaterial for improving salt tolerance of wheat, characterized in that: The preparation method comprises the following steps: S1. Ultrasonic mixing of the sulfur-containing biomass carbon source material, the strong oxidant and the alkaline solution in deionized water to obtain a mixed solution; S2, subjecting the mixed solution obtained in S1 to a hydrothermal reaction, and cooling to room temperature after the reaction to obtain a reaction solution; S3. The reaction solution obtained in S2 is filtered and dialyzed in sequence to obtain carbon-based nanomaterials.

2. The method for preparing a carbon-based nanomaterial for improving salt tolerance of wheat according to claim 1, characterized in that: The mass volume ratio of the sulfur-containing biomass carbon source material, the strong oxidant, the alkaline solution and the deionized water in S1 is (0.1-0.3) g: (0.3-1) mL: (0.3-1) mL: (18-28) mL.

3. The method for preparing a carbon-based nanomaterial for improving salt tolerance of wheat according to claim 2, characterized in that: The sulfur-containing biomass carbon source material is one or more of straw powder, seaweed, garlic and durian shell powder; the strong oxidant is a hydrogen peroxide solution with a mass fraction of 20.00-40.00% or a potassium permanganate solution with a mass fraction of 1.00-3.00%; the alkaline solution is a 0.5-1.6 mol·L -1 Sodium hydroxide solution, concentration 0.1-0.4 mol·L -1 of potassium hydroxide solution or ethylenediamine.

4. The method for preparing a carbon-based nanomaterial for improving salt tolerance of wheat according to claim 1, characterized in that: The temperature of the hydrothermal reaction in S2 is 150-200°C and the time is 4-8h.

5. The method for preparing a carbon-based nanomaterial for improving salt tolerance of wheat according to claim 1, characterized in that: The specification of the dialysis membrane used in the dialysis in S3 is 1000Da, and the dialysis time is 3-5h.

6. A carbon-based nanomaterial for improving salt tolerance of wheat, characterized in that: The carbon-based nanomaterial is prepared by the method for preparing a carbon-based nanomaterial for improving the salt tolerance of wheat as described in any one of claims 1 to 5.

7. Use of the carbon-based nanomaterial for improving salt tolerance of wheat as claimed in claim 6 in wheat germination under a high-salt environment.

8. The use of a carbon-based nanomaterial for improving salt tolerance of wheat according to claim 7, characterized in that: The salt content of the high-salt environment is 50-200 mmol·L -1 .